Harnessing Light-Emitting Diode technology for cutting-edge Photovoltaic module characterisation - Ira Devi Sara; Fikrel Jasman; Hafidh Hafidh; Amir Zaki Mubarak (Jurnal Polimesin, 2024)
Significant advancements in Light-Emitting Diode (LED) technologies, including the availability of high-power LEDs at reduced costs, have rendered them a highly desirable and dependable solar simulator. However, there are still challenges in designing LEDs as solar simulators to evaluate the characteristics of specific solar modules across different technologies and sizes, particularly regarding spectral composition and spatial uniformity of irradiation. This work seeks to develop a prototype LED solar simulator capable of generating uniform light with stability of at least 90% (class C) throughout an illumination area of 54 cm × 67cm for laboratory instructional applications. The employed procedures encompass the selection of high-power LED bulbs, thermal management, electrical design, prototype fabrication, and performance assessment. The International Electrotechnical Commission (IEC) 60904-9:20 standard delineates the performance criteria for solar simulators and serves as a framework for constructing LED solar simulators. The study's results demonstrate that the LED solar simulator prototype has been successfully constructed and is categorized as class C, exhibiting a light non-uniformity and stability level of 10%. The capacity to delineate the current and voltage of a 50 cm × 30 cm small solar module under specified irradiance and temperature circumstances may be attained with a mean absolute error percentage of 0.01 and a root mean square error of 0.21. The hexagonal configuration of the LED array offers advantages for light design, including modularity and ease of expansion to achieve a broader illumination area. This arrangement can serve as an invaluable instrument to enhance solar energy research and maximize the performance of photovoltaic devices under regulated conditions.